Not The Meta: A Screenplay on the Negative Consequences of Prejudices between Young Chinese-Indonesian and Javanese and How to Overcome Them - Sendria Immanuel Kristianto; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
Prejudice has long been a root cause of intergroup conflict worldwide, and Indonesia is no exception—particularly in the relationship between Chinese-Indonesians and Javanese. This creative thesis aims to explore the possible causes of prejudice, how it manifests in everyday situations, and how it can be overcome. In the form of a drama-comedy screenplay, this work uses Intergroup Anxiety Theory to explain why people may develop prejudice and Anxiety/Uncertainty Management Theory to show how people can mitigate it. The story follows Kevin, a Chinese-Indonesian student, who is paired with his Javanese classmate, Gilang, to compete in a Mobile Legends: Bang Bang tournament. Throughout the story, Kevin is challenged to reflect on and overcome his prejudice, eventually learning to manage his anxiety through mindfulness—a mindset of being open, curious, and aware of different perspectives. Through this creative piece, people can understand the harmful effects of prejudice on society and the meaningful benefits that come from overcoming it.